Determinants of social participation in patients living with systemic lupus erythematosus: the Psy-LUP multicentre study - Eric Hachulla; Nathalie Costedoat-Chalumeau; Nicolas Schleinitz; Antoine Huart; Viviane Queyrel; Nathalie Tieulie; Laurent Chiche; Aurelie Hummel; Noémie Jourde-Chiche; Eric Daugas; Jean-Robert Harle; Gilles Kaplanski; et al. (RMD Open)
Objective Systemic lupus erythematosus (SLE) can negatively impact patients’ social participation. The aim of this study was to identify the determinants of social participation in patients with SLE.Methods A cross-sectional evaluation was carried out in 100 adult outpatients with SLE enrolled in the multicentre psychosocial lupus (Psy-LUP) study. Participants completed the following standardised questionnaires: Participation Scale (social participation); Zimbardo Time Perspective Inventory; Sarason’s Social Support Questionnaire; Couples Satisfaction Index; Brief Illness Perceptions; Short Form-36 and Lupus-QoL. Stepwise multivariate regression analysis identified determinants of social participation.Results 92 women and eight men were included. Mean age was 44 years, mean SLE duration was 14 years, 52% of patients had a history of lupus nephritis and 38% were currently receiving immunosuppressants and/or biologics. 73% were in a couple and 64% were employed. Social participation was reduced in 29% of patients (compared with 46% in rheumatoid arthritis or multiple sclerosis), who reported different illness perceptions than those with preserved social participation. In multivariate linear regression, female sex (p=0.006), smoking (p=0.04), osteoporotic fractures (p=0.03), anti-cardiolipin antibodies (p=0.01) and ‘Past Negative’ time perspective (p=0.002) were associated with reduced social participation, while haematological involvement (p=0.005) and ‘Present Hedonistic’ time perspective (p=0.02) were protective. Reduced social participation was also associated with illness representations and with lower health-related quality of life (HR-QoL) scores.Conclusions Social participation is frequently altered in patients with SLE and correlates with illness representations, time perspective and HR-QoL. Psychological support and therapeutic education may help improve patients’ time perspective.Trial registration number NCT03913754.